Opportunities and challenges in GaN metal organic chemical vapor deposition for electron devices. (12th April 2016) - Matsumoto, Koh; Yamaoka, Yuya; Ubukata, Akinori; Arimura, Tadanobu; Piao, Guanxi; Yano, Yoshiki; Tokunaga, Hiroki; Tabuchi, Toshiya
Abstract: The current situation and next challenge in GaN metal organic chemical vapor deposition (MOCVD) for electron devices of both GaN on Si and GaN on GaN are presented. We have examined the possibility of increasing the growth rate of GaN on 200-mm-diameter Si by using a multiwafer production MOCVD machine, in which the vapor phase parasitic reaction is well controlled. The impact of a high-growth-rate strained-layer-superlattice (SLS) buffer layer is presented in terms of material properties. An SLS growth rate of as high as 3.46 µm/h, which was 73% higher than the current optimum, was demonstrated. As a result, comparable material properties were obtained. Next, a typical result of GaN doped with Si of 1 × 10 16 cm −3 grown at the growth rate of 3.7 µm/h is shown. For high-voltage application, we need a thick high-purity GaN drift layer with a low carbon concentration, of less than 10 16 cm −3 . It is shown that achieving a high growth rate by precise control of the vapor phase reaction is still challenge in GaN MOCVD.